Strategi pendidikan anti korupsi dalam menciptakan generasi bersih - Maula, Nilna Rohmatal (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that hinders development and undermines the social order. Therefore, systematic efforts are needed to foster intregity values from an early age through education. This study aims to analyze anticorruption education strategies to create a clean generation. The method used is a literature review by examining sources related to character education and anticorruption. The results of the study indicate that effective strategies include integrating anticorruption values into the curriculum, role modeling based learning, strengthening an honest and transparent school culture, and the active role of families and communities. Anticorruption education encompasses not only cognitive aspects but also affective and psychomotor aspects through the cultivation of honest, disciplined, and responsible behavior. By implementing this comprehensive strategy, it is hoped that a generation can be formed that is aware of the dangers of corruption and capable of becoming agents of change in realizing a clean and integrity based society.